Habitat‐specific positive and negative effects of soil biota on seedling growth in a fragmented tropical montane landscape. Issue 7 (25th February 2014) - Pizano, Camila; Mangan, Scott A.; Graham, James H.; Kitajima, Kaoru
<x xml:space="preserve">Abstract</x> Soil biota, in particular fungi and other microbes, are known to interactively influence plant community structure. However, soil biota effects that can be isolated in a greenhouse experiment may be overridden by other biotic and abiotic factors in the field. Here we conducted parallel greenhouse and field experiments and quantified how soil biota sampled at the habitat level affect the performance of potential host plants within and across neighboring habitat types (pastures, coffee plantations and forest fragments) in a montane region in Colombia. We hypothesized that the direction and strength of soil‐biota effects depend on the habitat where soil is sampled, focal plant's life history, and field environmental characteristics (soil nutrients, light). In a greenhouse experiment, we compared growth of 10 plant species with soil from home (where species typically occur) and foreign (where conspecific adults rarely occur) habitats, with or without soil sterilization. In the field, we conducted a reciprocal transplant experiment in which we suppressed soil fungi with the application of fungicide. In the greenhouse experiment, fast‐growing pasture grass and pioneer trees performed less well with live soil from their home, compared to foreign habitats, and such home disadvantage was reduced following soil sterilization. Home disadvantage associated with live soil biota was also detectable in the field experiment, although light conditions of grasslands and coffee plantations benefited growth of these fast‐growing species. In contrast, coffee and shade‐tolerant trees performed similarly or better with their home soils, and showed no response to soil biota suppression. Overall, the species‐and‐habitat specific soil biota effects detectable in the field experiment were similar in direction and relative strength to those from the greenhouse experiments. Our findings highlight the importance of habitat‐level plant–soil interactions and plant life history for the regeneration of natural forests and agricultural production in human‐modified landscapes.